Plasticity Induced in the Human Spinal Cord by Focal Muscle Vibration - Rocchi, Lorenzo; Suppa, Antonio; Leodori, Giorgio; Celletti, Claudia; Camerota, Filippo; Rothwell, John; Berardelli, Alfredo (Frontiers in Neurology, 2018)
The spinal cord (SC) has in the past been considered a hardwired system which responds to inputs in a stereotyped way. A growing body of data have instead demonstrated that the SC is able to retain information and modify its effector capabilities, showing activity-dependent plasticity. We investigated whether focal muscle vibration (fMV) induces plasticity in the SC by measuring changes in H-reflex (HR) recorded from flexor carpi radialis (FCR) and reciprocal inhibition (RI) at the wrist following fMV. To do so, we tested the effect of fMV applied over the FCR on FCR-HR and RI in healthy subjects. We also examined FCR-HR and RI after applying fMV over additional muscles (extensor carpi radialis (ECR), biceps brachialis (BB) and abductor pollicis brevis (APB). We verified the effect of FCR or ECR muscle contraction alone on HR and RI. Finally, we examined the effect of fMV over FCR on median nerve somatosensory evoked potentials (SEPs) and heteronymous HR (HHR) elicited by ulnar nerve stimulation. fMV of FCR induced a persistent decrease of FCR-HR without changes in RI; similar changes occurred following fMV over BB and APB. FMV of ECR induced a decrease in the first two phases of RI, leaving the third phase of RI and the FCR-HR unchanged. Sustained contraction of FCR or ECR did not influence FCR-HR or RI. Finally, fMV of FCR did not modify SEPs, whereas it decreased HHR. These findings suggest that fMV is able to induce specific patterns of spinal excitability changes depending on the site of vibration.